Types of injury of elite football players of the anatomical localization - Gümüs, M.; Akalýn, T. C.; Göktepe, M.; Gökdemir, K.; Çýplak, M. E.; Emektar, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In football which is one of the most popular branches of sport and which has become a huge industry with globalization, it i known that injury instances of elite players are quite high. It is also known that the injury risk in professional football is 1000 times higher than industrial work areas accepted as highly risky, besides it was reported that elite male footballers are facing 65-95% performancerestricting injuries within a season at least once. It is observed that injuries in football are 85% in low extremities. 15-20% of these injuries are in soft tissues, 53% in hips, 42% knee flexor and 52% are in knee extensor. When all these are taken into account, the type of injury and anatomic localization and both the prevention of the injuries and their treatment are of great importance. This study aims to analyze several factors that play role in the injury process of elite footballers and to determine the anatomic localization of types of injuries. Method: The participants of the study are 130 professional male footballers playing in Professional Leagues of Turkish Football Federation with a mean age of 20-29 (25.4±3,1) with 12.67±3.72 years of experience in football. The necessary permissions were taken from team authorities prior to the study and the medical departments of the teams were cooperated. The logs and reports recorded within the last year in formal matches and trainings were investigated. The data obtained was analyzed with SPSS for Windows 16.0 statistical software and the means, standard deviations ± and percentiles (%) were placed in tables. Findings It was found out that the 50 players participating our study underwent 43 injuries in sum and 4 of them were goalkeepers (9.3%), 10 of them were defence players (23,3%), 16 of them were midfield players (37,2%), and 13 of them were forward position players (30.2%). When the injuries are analysed in terms of anatomical positions, out of these 43 injuries, it was observed that 3 (7%) were in head and neck parts, 13 (30.2%) were in high extremity part and 27 (62.8%) were in lower extremity part. When the injury frequencies were analyzed according to the players` positions, it was observed that goalkeepers got injured 4 (9.3%) times, defence players got injured 10 (23.3%) times, midfield players got injured 16 (37.2%) times and forward players got injured 13 (30.2%) times. Discussion: The findings obtained are supporting the data in the literature. Great majority of footballers underwent injuries due to a number of reasons. Players in midfield and forward positions are facing more injuries. In terms of anatomical positions, more injuries were observed in lower extremity part and in feet, ankles and around knees. The most frequently observed types of injuries are muscle abduction, torn muscles and sprain.